Determinants of Effective Tax Rates in Indonesia - Yudha Aryo Sudibyo; Icuk Rangga Bawono (The Indonesian Journal of Accounting Research, 2016)
Abstract: This study examines the determinants of effective tax rates (ETR) in Indonesia. The previous studies of ETR showed inconsistent results in various countries. Politics and economic factors influence the results of tax research especially between developing and developed countries. OLS regression was used to test the determinants of ETR, while two ETR measurements were used based on accrual and cash tax expense for robustness test. The relationship between firm size and ETR is explained by political power theory which shows the negative association. This result indicates that large firms paid lower corporate taxes than the small firms. The government provides more tax incentives to large firms and expects to attract more investment from them. The association between inventory intensity and ETR shows a positive coefficient of a 0.01 significance level when ETR2 is used as dependent variable. However, we have no substantial evidence to support the association between capital intensity and ETR. The industry effect shows a positive coefficient on the media and communication sector; agriculture, forestry, and fishing sector; as well as the manufacturing sector.Abstrak: Penelitian ini mengkaji faktor-faktor penentu tarif pajak efektif (ETR) di Indonesia. Studi sebelumnya dari ETR menunjukkan hasil yang tidak konsisten di berbagai negara. Faktor politik dan ekonomi mempengaruhi hasil penelitian pajak terutama antara negara berkembang dan negara maju. Regresi OLS digunakan untuk menguji determinan ETR, sementara dua pengukuran ETR digunakan berdasarkan biaya pajak akrual dan tunai untuk uji ketahanan. Hubungan antara ukuran perusahaan dan ETR dijelaskan oleh teori kekuatan politik yang menunjukkan hubungan negatif. Hasil ini menunjukkan bahwa perusahaan besar membayar pajak perusahaan yang lebih rendah daripada perusahaan kecil. Pemerintah memberikan insentif pajak lebih banyak kepada perusahaan-perusahaan besar dan mengharapkan untuk menarik lebih banyak investasi dari mereka. Hubungan antara intensitas inventori dan ETR menunjukkan koefisien positif dari tingkat signifikansi 0,01 ketika ETR2 digunakan sebagai variabel dependen. Namun, kami tidak memiliki bukti kuat untuk mendukung hubungan antara intensitas modal dan ETR. Pengaruh industri menunjukkan koefisien positif pada sektor media dan komunikasi; sektor pertanian, kehutanan dan perikanan; serta sektor manufaktur.